Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."–Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art